Experimental hypothyroidism during pregnancy affects nociception and locomotor performance of offspring in rats. (27th March 2013) - Alves, I.G.N; da Cruz, K.M.L; Mota, C.M.D.; de Santana, D.S.; Gaujac, D.P.; de Carvalho, V.C.B.; Reis, L.C.; Sluka, K.A.; Quintans‐Junior, L.J.; Antoniolli, A.R.; DeSantana, J.M.; Badauê‐Passos, D.; et al.
Abstract: Background: Thyroid hormones (THs) play a crucial role in the development of several organic systems. An adequate support of maternal THs may be required to ensure a normal nociceptive function of offspring into adulthood. We investigated the impact of experimental gestational hypothyroidism (EGH) on nociceptive threshold and motor performance in the offspring at different post‐natal days (PND) in both male and female rats. Methods: EGH was induced by the administration of 0.02% methimazole (MMI) in the drinking water from the ninth day of gestation until birth. The offspring from MMI‐treated dams (OMTDs) or from water‐treated dams (OWTDs) were assessed for thermal and mechanical nociception using the tail‐flick test and von Frey filaments, respectively. Both rota‐rod and grip strength were used to assess motor function. Results: OMTD had reduced thermal ( p < 0.05) but not mechanical threshold at all studied ages (60 and 120 PND). Sixty‐day‐old OMTD presented reduced latency to the tail‐flick test ( p = 0.01). Grip strength in 120‐day‐old OMTD was reduced ( p < 0.01). However, only male OMTD presented a lower locomotor performance on the rota‐rod test when analysed on the 60th PND ( p < 0.01). Conclusions: EGH promotes hypersensitivity to noxious thermal but not mechanical stimulus. Moreover, motor force is similarly reduced in male and female OMTDs, whereas motor performance is reduced only in mature male OMTD, suggesting the presence of a protective factor in females.